Śāntarakṣita on veridical perception - Friquegnon, Marie Louise (Acta Orientalia Vilnensia, 2010)
William Paterson University Śāntarakṣita, an 8th century Indian Buddhist philosopher, united the Cittamātra and the Madhyamaka views into a single system. Consistently following Nāgārjuna, from the point of view of absolute reality he proclaimed all things to be empty and beyond conception. From the point of view of the conventional, he stated that we should understand everything as awareness. Nevertheless, when analysing Cittamātra views on perception, he found them all to be inadequate. Buddhism is usually described as based on two pillars, direct experience and inference. Given Śāntarakṣita’s sharp critique of the veracity of perception, upon which inductive premises are based, how are we to make sense of knowledge on the conventional level? I will attempt to answer this question through an analysis of the ideas of the 11th century philosopher Rongzom and the 19th century philosopher Mipham. I will also show the relevance of Śāntarakṣita’s critique of perception today, by comparing it with contemporary Western cognitive science.